Revisiting aspiration and ability in international migration - Carling, Jørgen; Schewel, Kerilyn (Journal of ethnic and migration studies, 2018)
It is a refreshingly simple thought that migration is the combined result of two factors: the aspiration to migrate and the ability to migrate. Without having to resort to overly structural or individualistic explanations, this analytical distinction helps disentangle complex questions around why some people migrate but others do not. Still, aspiration and ability raise their own thorny theoretical and methodological questions. To begin with, what does it mean to have migration aspirations? How can such concepts be objects of empirical research? And is it meaningful to say that individuals possess the ability to migrate if their preference is to stay? The aspiration/ability model was originally proposed in this journal and has since been diversely applied and adapted. In this article, we look back at more than a decade of research to examine a series of theoretical and empirical developments related to the aspiration/ability model and its extensions. We identify two-step approaches as a class of analytical frameworks that share the basic logic of the aspiration/ability model. Covering expansive theoretical, methodological and empirical ground, we seek to lay a foundation for new research on global migration in its diverse forms.